Estudio de factibilidad para la creación de un centro de nutrición infantil de niños menores de cinco años con apadrinamiento, parroquia San Camilo, cantón Quevedo, año 2015 - Quiroz Guevara, Karla Estefanía (2015)
This research had as main objective, conduct a feasibility study for the creation of a Centre for Child Nutrition children five years with sponsorship, parish San Camilo, Quevedo Canton, and tries to compensate for unmet needs of the population, the same as will feature quality schemes, affordable, and dedicated one hundred percent to meet the objectives. The contextualization of the problem, analyze the current situation through the statement of the problem, formulation of objectives and proper justification of the research. The results found by a market study identified a need unmet about Child Nutrition center at St Camillus, Quevedo Canton is presented. The technical study helped identify the optimal location of the center, infrastructure, equipment, materials and inputs necessary for the operational process., through economic study showed that there net profits for all the years of the life of the project and through the financial assessment profitability is verified with a Net (NPV) Present Value of $ 129.589,41 and an Internal Rate of Return (IRR) of 41.49%. Keywords Feasibility study, health nutrition, infant nutrition, sponsorship